(untitled) (Faculty of Education Scientific Journal, 2025)
In this study, the researcher deals with one of the most important topics related to the science of grading hadiths and judging them, which is the steps of scientific grading: collection, comparison, and interpretation, by explaining how to apply each step, giving examples, and showing the benefits gained from collection, explaining the method of drawing the chain of transmission tree, and the effects resulting from conducting the comparison process from determining the main orbit around which the hadith revolves, and the rest of the other sub-orbits, and monitoring the state of the narration in terms of uniqueness, agreement, or disagreement, and determining the type of disagreement, and from whom it occurred, and explaining the method of interpretation the narrator from whom the uniqueness or disagreement occurred, all of this in order to achieving the main objective of scientific grading. The study concluded that all of these steps must be applied to every hadith that is to be graded, and that the most important of these steps is the collection step, as it is the basis for the remaining steps, and that the interpretation is not for all narrators, and the narrator’s interpretation is limited to what serves the topic of the hadith only. May ALLAH bless and grant peace to our master Mohammed, his Family and his Companions.